2011
DOI: 10.1007/s10640-010-9452-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms and Behavior in the Local Commons as Seen Through the Lens of Field Experiments

Abstract: Laboratory and field experiments, Common-pool resources, Collective action, Regulations, Social norms, C93, D01, H39, H41, Q2, Q56, Q57,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 56 publications
1
43
1
1
Order By: Relevance
“…The only variable consistently significant across the three models is attends water meetings, implying if the respondent attended water meetings they were more likely to have experienced past conflict and expect to experience future conflict and future physical violent conflict. This result appears contradictory to the findings of past studies on informal mechanisms for resource management, attending meetings shares a positive relationship with conflict [35,56,57]. These studies showed that when communication or positive informal rules and social norms were present, more socially optimal outcomes were achieved.…”
Section: Independent Variables Used In the Modelcontrasting
confidence: 85%
See 1 more Smart Citation
“…The only variable consistently significant across the three models is attends water meetings, implying if the respondent attended water meetings they were more likely to have experienced past conflict and expect to experience future conflict and future physical violent conflict. This result appears contradictory to the findings of past studies on informal mechanisms for resource management, attending meetings shares a positive relationship with conflict [35,56,57]. These studies showed that when communication or positive informal rules and social norms were present, more socially optimal outcomes were achieved.…”
Section: Independent Variables Used In the Modelcontrasting
confidence: 85%
“…The specification of water as the source of the dispute explores directly whether water is observed as a source of friction. Despite less than two percent of respondents naming water as a source of conflict (see Figure 4), 57.6% reported observing a dispute over water. Perceptions of future water disputes can also indicate respondent's sense and expectation of water security.…”
Section: Independent Variables Used In the Modelmentioning
confidence: 99%
“…In particular, economic field experiments with users who share a real natural resource have increased our knowledge regarding how they make decisions and self-organize to extract those resources in a sustainable way (Cárdenas, 2000(Cárdenas, , 2011Cárdenas and Carpenter, 2008;Cárdenas and Ostrom, 2004;Janssen and Anderies, 2011;Muradian and Cárdenas, 2015;Ostrom, 2006), thus avoiding the circumstance of being trapped in the "tragedy of the commons" (Hardin, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Common pool resource (CPR) experiments using subjects who share a real natural resource, e.g., an artisanal fishery, have provided valuable insights in particular (Cárdenas 2003, 2004, 2009, 2011Cárdenas and Ostrom 2004, Rodríguez-Sickert et al 2008. Because the subjects, e.g.…”
Section: Introductionmentioning
confidence: 99%